ÐœÐ¾Ñ€Ñ„Ð¾Ð»Ð¾Ð³Ð¸Ñ‡ÐµÑÐºÐ¸Ðµ Ð¸Ð·Ð¼ÐµÐ½ÐµÐ½Ð¸Ñ ÑÑ€Ð¸Ñ‚Ñ€Ð¾Ñ†Ð¸Ñ‚Ð¾Ð² Ð¶Ð¸Ð²Ð¾Ñ‚Ð½Ñ‹Ñ… Ð¿Ð¾ÑÐ»Ðµ ÐºÑ€Ð¸Ð¾ÐºÐ¾Ð½ÑÐµÑ€Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð¸Ñ - Denisova, O. N.; Kuleshova, L. G.; Zemlyanskikh, N. G.; Babijchuk, L. A.; Zhegunov, G. F. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2007)
Morphological changes in equine, bovine, and canine erythrocytes, when interacting with 20% dimethylsulfoxide (DMSO) and 30% polyethylene oxide with molecular mass of 1500 (PEO-1500) solutions, as well as after cell cryopreservation at the presence of the mentioned cryoprotectants have been studied in this research using light microscopy. Frozen-thawed erythrocytes of all animal species were established to be transformed into echinocytes under DMSO penetrative cryoprotectant effect and into stomatocytes under a non-penetrative one. The state of animal frozen-thawed erythrocytes when transferring them into physiological conditions was analysed.